PENGARUH KONSENTRASI STABILIZER HPMC SS12 TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK MAYONESSUSU KEDELAI REDUCED FAT - Angkadjaja, Anita; Suseno, Thomas Indarto Putut; ., Lynie (Jurnal Teknologi Pangan dan Gizi, 2014)
Mayonnaise also can be made from soymilk in substitution with egg yolk as natural emulsifier and also can reduce the fat content which can be prone to human’s health condition. During the mayonnaise processing, stabilizer, HPMC (Hydroxypropyl Methylcellulose) is need so mayonnaise will become more stable and also resulted in good organoleptic texture. Research is need to know the effect of HPMC to mayonnaise physicochemical and organoleptic texture. The experimental design used is randomized group design with single factor which is SS12 concentration divided into 7 (seven) levels of SS12 concentration and repeated 4 (four) times. The parameters analyzed are emulsion stability, viscocity, density b/v, color, organoleptic, water content, and texture characteristic with Texture Profile Analyzer, pH, and fat content. All data will be processed stastically with ANOVA (Analysis of Variance) on α = 5% and if there is a significance difference, the data will be processed stastically with Duncan’s Multiple Range Test to know the level of concentration which give the most significance difference. The result showed that the difference in the concentration of stabilizer HPMC SS12 was significantly affected of the water content, density, organoleptic (taste) but no significant effect on the pH, viscocity, texture (firmness and cohesiveness), and organoleptic (mouthfeel and appearance). The best treatment was obtained at concentration of 3.5% stabilizer HPMC SS12 with pH 4.75, viscocity 14983.3333 cP, water content 29.35% (wb), density 0.9435 g/mL, firmness 85.9887 N, cohesiveness 67.7812 N, and fat content 47.51%.